Tinjauan Tinjauan Aspek Keamanan dan Kerahasiaan Rekam Medis di Ruang Filling Puskesmas Cipatat Bandung - Rika Miftah Nurul Azizah; Ade Irma Suryani (Politeknik Negeri Jember, 2023)
The objective of this study was to know the confidentiality and security aspects of the medical records in the archives room of the Puskesmas Cipatat Kabupaten Bandung Barat. This study was conducted at Puskesmas Cipatat. This research method uses qualitative descriptive method, the data collection techniques used are observation, literature study and questionnaire. Search results are safety aspects of medical records in the records room, specifically tracer, AC, coil o pack, ticks, insects present in the records room and also food or waste drinks, dust in the filling room. Meanwhile, APAR, thermometer, camphor, leaky roof and direct (ultraviolet) sunlight shining on the surface of medical record documents in room records showed no fungi in the room profile. For the private aspects of the medical records in the room record, i.e. having agents other than the medical record enter the records room, there are no medical record documents brought in by the patient, lack of medical records, as well as the doctors and nurses that keep the contents of the medical records therein. There is no security device in the room like CCTV.